Economic development, cargo handling methods and labour process change: the place of the Vietnamese dock worker in the 'global' history of dock work. (2nd January 2021) - Taylor, Greig; Nguyen, Thanh-Thuy; Mathew, Sagi K.; Nguyen, Lan Thi
ABSTRACT: The advent of containerised cargo completely revolutionised shipping and world trade, also transforming the way that dock workers did their jobs. As a result, the docks are one of the most academically scrutinised industries. However, much of the research in this stream is limited to developed countries. Just as the economies of South East Asia are expanding rapidly and gaining increased attention, so more emphasis needs to be placed on the way economic growth and modernisation affect management, employment and administration of key industries in these countries. To these ends, this article will explore the modernisation of the Vietnamese dock industry and examine whether workers there have experienced similar challenges as their counterparts elsewhere, despite the country's very different path and timing of economic development.